Experimental study on the evolution of submerged artificial sandbar-beach profile under the regular waves condition - Zhang, Wenliang; Guo, Junli; Shi, Lianqiang; Liu, Zhuocheng; Ye, Qinghua; Kuang, Cuiping; Peng, Yu; Qi, Huangzhe (Frontiers in Marine Science, 2025)
Submerged artificial sandbars (SABs) are increasingly favored as an efficient method for beach nourishment, helping to mitigate beach erosion and maintain the sediment transport budget, thus promoting ecological stability. A comprehensive understanding of the morphodynamical evolution of the submerged artificial sandbar-beach profile is essential. This study employs a scaled-down moving-bed flume test to examine the dynamic geomorphological evolution of the submerged artificial sandbar-beach system under regular wave conditions. Twenty experiments, each with different wave heights and periods representative of the Zhejiang coast, were conducted. The study investigated the profile evolution and wave parameters of the submerged artificial sandbar-beach model. The results reveal low wave reflection in front of the sandbar, indicating that under the tested wave conditions, the sandbar primarily serves as a sediment source rather than effectively reflecting wave energy. In all scenarios, the top of the sandbar migrates shoreward, and the sandbar’s contour shape becomes asymmetric. For smaller wave periods, localized erosion occurs in the troughs, while larger periods result in complete siltation. Continuous sediment transport into the trough characterizes the beach face, with sediment movement controlled by wave height and period. A linear or nonlinear relationship between sandbar erosion depth, beach slope, and wave parameters (height, period) is established, providing an empirical model for SAB-beach profiles. These findings enhance the understanding of SAB-beach systems and offer valuable insights for coastal protection and disaster prevention in engineering applications.